Coal gasification through microbial degradation in a low-pressure CO2 and H2 environment: An experimental study - Kuo JIAN; Xuehai FU; Mingjie LIU; Jian LIU; Jin LI; Zhongliang RU; Xiaofeng JI; Qiang WANG (Meitian dizhi yu kantan)
Objective and MethodsThis study aims to investigate the characteristics of CO2 biomethanation and coal gasification through microbial degradation in a low-pressure environment. With low-rank bituminous coals (Rmax = 0.67%) as fermentable substrates, this study conducted a 96-day gas production experiment through microbial fermentation in a low-pressure CO2 and H2 environment. Using techniques including gas chromatography, 16S rRNA gene sequencing, and low-temperature liquid nitrogen adsorption, this study delved into the intrinsic variation patterns of biogenic gas production, microbial communities, and coal structures. Results and Conclusions The results indicate that compared to conventional fermentation, the injection of low-pressure CO2 inhibited CH4 production, leading to a reduced CH4 production efficiency. After the H2 injection, the injected H2 was consumed quickly, resulting in a rapid decrease in the H2 concentration and contributing to CH4 production. Meanwhile, the H2 injection changed the production mode of biogenic gas, exerting a profound influence on the structure of microbial communities in fermentable liquids. Specifically, the relative abundance of Firmicutes and Bacteroidota increased. Notably, the S50_wastewater_sludge_group in Bacteroidota always predominated, trending upward together with the unclassified_W27 genus. This occurred due to the late-stage H2 injection, which accelerated the growth and metabolism of both bacterial genera. Regarding the distribution of archaea at the genus level, Methanobacterium represented the highest proportion (47.66%‒83.05%), followed by Methanosarcina and Methanoculleus sequentially. Benefiting from the simultaneous consumption of H2, CO2, and substrates such as acetic acid, the relative abundance of Methanosarcina exhibited a significant upward trend. In contrast, Methanoculleus, which synthesizes methane via the hydrogenotrophic pathway, displayed a rapidly decreasing relative abundance due to a shortage of H2 in the later stage. Compared to the raw coals, coals with injected low-pressure CO2 exhibited a lower adsorption capacity, with the total pore volume and specific surface area decreasing. As more low-pressure CO2 was injected, fractal dimensions D1 and D2 trended downward and upward, respectively, suggesting an increase in the surface roughness of coal pores and a decrease in the complexity/heterogeneity of pore structures. This is inferred to be associated with the dual effects of microbial degradation and carbonate precipitation. The results of this study enrich the fundamental theories on the microbial degradation of coals and the biological transformation and utilization of CO2, especially providing a theoretical basis for the biological transformation and storage of CO2 in coal seams.